1992
DOI: 10.1677/joe.0.1340405
|View full text |Cite
|
Sign up to set email alerts
|

Sex hormone concentrations in blood serum from the North Atlantic fin whale (Balaenoptera physalus)

Abstract: Blood serum concentrations of testosterone and progesterone were measured in postmortem samples taken at sea from 814 fin whales (Balaenoptera physalus) caught during the summers (June-September) of 1981-1989. The ages of 781 of these animals were also assessed. The testosterone concentrations in samples from 352 males averaged 2 nmol/l; 41 samples had concentrations of 0.1 nmol/l or lower and 34 of these came from whales aged between 2 and 14 years and showed a Gaussian type of age distribution with a peak nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 8 publications
6
31
2
Order By: Relevance
“…However, serum T and P concentrations were mostly undectable in immature males as well as mature males and immature females, respectively. This is contrary to our own findings for two other species of the same genus, the northern fin whale (Kjeld and Árnason 1990;Kjeld et al 1992) and the sei whale (Kjeld et al 2003), both of which showed significant increases of serum T concentrations during the hunting season.…”
Section: Introductioncontrasting
confidence: 96%
See 1 more Smart Citation
“…However, serum T and P concentrations were mostly undectable in immature males as well as mature males and immature females, respectively. This is contrary to our own findings for two other species of the same genus, the northern fin whale (Kjeld and Árnason 1990;Kjeld et al 1992) and the sei whale (Kjeld et al 2003), both of which showed significant increases of serum T concentrations during the hunting season.…”
Section: Introductioncontrasting
confidence: 96%
“…This comparison applies to the North Atlantic fin whale (Kjeld et al 1992) and sei whale (Kjeld et al 2003) in both of which serum P concentrations have been measured.…”
Section: Introductionmentioning
confidence: 99%
“…For the females, as expected, pregnant animals had much higher levels of progesterone than non-pregnant individuals. Mean progesterone levels (0.054 ng ml −1 ) in immature animals were in line with those reported in other baleen whales: minke whales Balaenoptera acutorostrata, < 0.02 to 1.50 ng ml −1 (Su zu ki et al 2001, Kjeld et al 2004, Birukawa et al 2005; sei whales Balaenoptera borealis, < 0.04 ng ml −1 (Kjeld et al 2003); and fin whales Balaenoptera physalus, < 0.04 ng ml −1 (Kjeld et al 1992, Kjeld 2001. However, the mean value for the serum in the pregnant bowhead whales (31.6 ng ml −1 ) in the present study was substantially higher than mean values seen in other pregnant baleen whales: minke whales, 6.71 to 13.8 ng ml −1 (Suzuki et al 2001, Kjeld et al 2004, Birukawa et al 2005; and sei whales, 3.24 to 6.60 ng ml −1 (Kjeld et al 2003, Birukawa et al 2005.…”
Section: Serum Progesteronesupporting
confidence: 84%
“…However, the bulk of mammalian endocrine literature reports steroid hormone levels from blood (Temte 1991, Kjeld et al 1992, Atkinson et al 1999 and to a lesser degree urine (Robeck et al 1993), feces (Rolland et al 2005(Rolland et al , 2006, and saliva (Atkinson et al 1999, Hogg et al 2005). Other sample materials from which these hormones have been extracted and measured include milk (West et al 2000), muscle (Yoshioka et al 1994), cetacean exhalant or blow (Hogg et al 2005), bone, and ocular secretions (Atkinson et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Lifetime profiles offer significant improvements over costly ship time and conventional intermittent sampling techniques that use blood (39), feces (40), blubber (41)(42)(43), morphometric measurements, and/or exhalations (4) as well as conservation advantages in the reduction in the samples (blood, blubber, etc.) required to address a specific research question (3,41).…”
Section: Discussionmentioning
confidence: 99%